Sidney Sheldon's The Tides of Memory [compact disc, unabridged] - Bagshawe, Tilly (Dreamscape Media, 2013)
Fixtures on the society pages, in international boardrooms, and in the highest echelons of government, the members of the powerful De Vere family lead charmed and envied lives, moving between their London mansion, Oxfordshire country house, and exclusive Martha's Vineyard estate, when they are not jet-setting around the globe. But beneath their gilded facade and seemingly unbreakable familial bonds lie secrets, ugly, dirty, and deadly.